Integrating Scrabble Online as a Tool To Support for Vocabulary Learning - Ayumi Pratiwy Tanjung; Rahmah Fithriani (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
Scrabble online is an application that can be used to teach vocabulary. In this particular study, researchers used online scrabble on students from a high school in Simalungun. There were six participants in this study. The purpose of this study is to find out how students feel about the effectiveness of using online scrabble to improve their vocabulary. The question that needs to be answered in this study is,